Effects of a Dark Septate Fungal Endophyte on the Growth and Physiological Response of Seedlings to Drought in an Epiphytic Orchid - Liu, Na; Jacquemyn, Hans; Liu, Qiang; Shao, Shi-Cheng; Ding, Gang; Xing, Xiaoke (Frontiers in Microbiology, 2022)
Dark septate endophytes (DSE) are a group of facultative biotrophic root-colonizing fungi that live within a plant for a part of their life cycle without causing any apparent, overt negative effects. These fungi have been found in >600 different plant species, including orchids. Although the precise ecological functions of dark septate fungal endophytes are not yet well understood, there is increasing evidence that they enhance host growth and nutrient acquisition, and improve the plant's ability to tolerate biotic and abiotic stresses. In this research, we tested the effects of a DSE isolated from the roots of the epiphytic orchid Coelogyne viscosa on the growth and drought tolerance of orchid seedlings. Our results showed that addition of DSE inoculum significantly enhanced biomass of seedlings and increased the activities of drought resistance related enzymes and the accumulation of osmoregulatory substances. These results suggest that DSE can fulfil important ecological functions in stressful environments and potentially play an important role in the life cycle of epiphytic orchids.